2014
DOI: 10.1242/jcs.148619
|View full text |Cite
|
Sign up to set email alerts
|

Probing the biomechanical contribution of the endothelium to lymphocyte migration: diapedesis by the path of least resistance

Abstract: Immune cell trafficking requires the frequent breaching of the endothelial barrier either directly through individual cells ('transcellular' route) or through the inter-endothelial junctions ('paracellular' route). What determines the loci or route of breaching events is an open question with important implications for overall barrier regulation. We hypothesized that basic biomechanical properties of the endothelium might serve as crucial determinants of this process. By altering junctional integrity, cytoskel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
148
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(164 citation statements)
references
References 70 publications
(105 reference statements)
14
148
0
Order By: Relevance
“…Briefly, an increase in endothelial cell contractility through Rho mechanisms is recognized to play a major role in control of the endothelial permeability barrier. Recently, it was shown that endothelial cell stiffness per se plays a role in adhesion and transmigration of immune cells (84,85). Our previous studies also demonstrate that an increase in endothelial cell stiffness and force generation enhances endothelial angiogenic potential in 3D cultures in vitro (10,11) and in matrigels inserted in vivo (56).…”
Section: Impact Of Oxidized Lipids On Endothelial Membrane Lipid Packmentioning
confidence: 55%
“…Briefly, an increase in endothelial cell contractility through Rho mechanisms is recognized to play a major role in control of the endothelial permeability barrier. Recently, it was shown that endothelial cell stiffness per se plays a role in adhesion and transmigration of immune cells (84,85). Our previous studies also demonstrate that an increase in endothelial cell stiffness and force generation enhances endothelial angiogenic potential in 3D cultures in vitro (10,11) and in matrigels inserted in vivo (56).…”
Section: Impact Of Oxidized Lipids On Endothelial Membrane Lipid Packmentioning
confidence: 55%
“…24 To find these spots of low resistance, lymphocytes dynamically probe the underlying endothelium by extending invadosome-like protrusions into its surface that deform the plasma membrane, depolymerize F-actin filaments at the membrane cortex and ultimately breach the barrier. 24,25 The authors suggest that leukocyte transmigration is guided by a common principle namely 'the path of least resistance'. 24 However, determining where the path of least resistance is present in vivo is very difficult, if not impossible.…”
Section: Tenertaxismentioning
confidence: 99%
“…24,25 The authors suggest that leukocyte transmigration is guided by a common principle namely 'the path of least resistance'. 24 However, determining where the path of least resistance is present in vivo is very difficult, if not impossible. The observations of tenertaxis for TEM are so far only performed in in vitro studies.…”
Section: Tenertaxismentioning
confidence: 99%
See 1 more Smart Citation
“…Leukocytes probe the surface of the substrate (i.e. ECs) and sense local EC stiffness through ventral filopodia or invadosome-like protrusions Martinelli et al, 2014;Schaefer et al, 2014;Shulman et al, 2009). The mechanosensitive response of leukocytes to substrate stiffness is mediated by their integrins, which are force-generating mechanoreceptors (Roca-Cusachs et al, 2012;Ross et al, 2013).…”
Section: Mechanotransduction In Leukocytesmentioning
confidence: 99%